2020
DOI: 10.3390/molecules25245822
|View full text |Cite
|
Sign up to set email alerts
|

Ionone Is More than a Violet’s Fragrance: A Review

Abstract: The term ionone is derived from “iona” (Greek for violet) which refers to the violet scent and “ketone” due to its structure. Ionones can either be chemically synthesized or endogenously produced via asymmetric cleavage of β-carotene by β-carotene oxygenase 2 (BCO2). We recently proposed a possible metabolic pathway for the conversion of α-and β-pinene into α-and β-ionone. The differences between BCO1 and BCO2 suggest a unique physiological role of BCO2; implying that β-ionone (one of BCO2 products) is involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 127 publications
1
41
0
2
Order By: Relevance
“…Sneezing occurs because of the activation of these sensory fibers (expressing TRPA1 and TRPV1) in the vagal sensory nerve terminals by noxious stimulants [ 4 ]. Signal transduction occurs by augmenting intracellular calcium concentrations and/or depolarizing membrane potentials [ 137 , 138 ]. It was found that there is an overexpression of TRPV1 in the nasal mucosa and augmented substance P levels in nasal secretions in idiopathic rhinitis patients [ 139 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sneezing occurs because of the activation of these sensory fibers (expressing TRPA1 and TRPV1) in the vagal sensory nerve terminals by noxious stimulants [ 4 ]. Signal transduction occurs by augmenting intracellular calcium concentrations and/or depolarizing membrane potentials [ 137 , 138 ]. It was found that there is an overexpression of TRPV1 in the nasal mucosa and augmented substance P levels in nasal secretions in idiopathic rhinitis patients [ 139 ].…”
Section: Discussionmentioning
confidence: 99%
“…The specific oxidative cleavage of carotenoids at (9,10 and 9',10') leads to the production of β-ionone and is catalyzed by a carotenoid cleavage dioxygenase (CCD1) (Figure 1) [13][14][15]. The biosynthesis of β-ionone in general in the plant kingdom has been recently intensively reviewed by Shi et al [57] and Aloum et al [58].…”
Section: Biosynthesis Of β-Iononementioning
confidence: 99%
“…Plant apocarotenoids, including β-ionone, comprise flavors, aromas, pigments, growth regulators, and defense compounds. They serve as ecological cues, have roles as insect attractants or repellants, and possess antibacterial and fungicidal properties [57,58,70]. β-Ionone and other apocarotenoid pigments are also economically important because they show extremely potent odor thresholds, at a level of 0.007 ppb.…”
Section: Role Of β-Ionone In Plantsmentioning
confidence: 99%
See 2 more Smart Citations